Analisis Faktor - Faktor Yang Mempengaruhi Return Saham (Kasuspada Perusahaan Manufaktur yang Go Public di BEI periodetahun 2010 - 2013) - Syeh, Muhammad; , Drs. Agus Endro Suwarno, M.Si (2016)
This study aims to determine the factors that affect its on stock returns in the manufacturing companies that go public in BEI period 2010-2013. Financialratios in this study is, Return on Assets (ROA),), Debt to Equity Ratio (DER), Total Assets Turnover (TATO), Price to Book Value (PBV), Current ratio (CR). This research was conducted with a purposive sampling method to obtain a representative sample in accordance with predetermined criteria. The number ofsamples obtained are as many as 88 companies mining the study period 2010-2013. The methods used to analyze the data is multiple linear regression analysismethod. The results of this study indicate that the Return on Assets (ROA) affects stockreturns, Debt to Equity Ratio (DER) has no effect on stock returns, Total Assets Turnover (TATO) has no effect on stock returns, Price to Book Value (PBV) effect on stock returns, and the current ratio (CR) has no effect on stock returns.